Control system design for a novel minimally invasive surgical robot. (16th December 2016) - Ai, Yue; Pan, Bo; Fu, Yili; Wang, Shuguo
Abstract: A novel separate robotic system for minimally invasive surgery (MIS) has been presented in this paper. Control system architectures were designed, basing on versatile performance criteria. The compact control and mechanical structure were suitable for medical environment. Function and safety design satisfying medical application were integrated into the robot system as well. Additionally, intuitive control algorithm solved the problems of hand-eye incoordination and workspace mismatch between master hands and slave arms during the master–slave control process. A series of experiments have been accomplished to evaluate the performance of the robotic system at last. The results demonstrated that the robotic system was capable of executing surgical operation intuitively and implementing auxiliary functions perfectly, which meant that the control system was feasible and reliable.